Sacubitril/valsartan attenuates atrial conduction disturbance and electrophysiological heterogeneity with ameliorating fibrosis in mice - Iwamiya, Satoshi; Ihara, Kensuke; Furukawa, Tetsushi; Sasano, Tetsuo (Frontiers in Cardiovascular Medicine, 2024)
Background Sacubitril/valsartan (SacVal) has been shown to improve the prognosis of heart failure; however, whether SacVal reduces the occurrence of atrial fibrillation (AF) in heart failure has not yet been elucidated. In this study, we aimed to determine whether SacVal is effective in reducing the occurrence of AF in heart failure and identify the underlying mechanism of its electrophysiological effect in mice. Methods Adult male mice underwent transverse aortic constriction, followed by SacVal, valsartan, or vehicle treatment for two weeks. Electrophysiological study (EPS) and optical mapping were performed to assess the susceptibility to AF and the atrial conduction properties, and fibrosis was investigated using heart tissue and isolated cardiac fibroblasts (CFs). Results EPS analysis revealed that AF was significantly less inducible in SacVal-treated mice than in vehicle-treated mice. Optical mapping of the atrium showed that SacVal-treated and valsartan-treated mice restored the prolonged action potential duration (APD); however, only SacVal-treated mice showed the restoration of decreased conduction velocity (CV) compared to vehicle-treated mice. In addition, the electrophysiological distribution analysis demonstrated that heterogeneous electrophysiological properties were rate-dependent and increased heterogeneity was closely related to the susceptibility to AF. SacVal attenuated the increased heterogeneity of CV at short pacing cycle length in atria, whereas Val could not. Histological and molecular evaluation showed that SacVal exerted the anti-fibrotic effect on the atria. An in vitro study of CFs treated with natriuretic peptides and LBQ657, the metabolite and active form of sacubitril, revealed that C-type natriuretic peptide (CNP) combined with LBQ657 had an additional anti-fibrotic effect on CFs. Conclusions Our results demonstrated that SacVal can improve the conduction disturbance and heterogeneity through the attenuation of fibrosis in murine atria and reduce the susceptibility of AF in heart failure with pressure overload, which might be attributed to the enhanced function of CNP.